2017
DOI: 10.1186/s12913-017-2262-8
|View full text |Cite
|
Sign up to set email alerts
|

Health care providers’ perspectives regarding the use of chlorhexidine gel for cord care in neonates in rural Kenya: implications for scale-up

Abstract: BackgroundThis paper explores the perspectives of health care providers regarding the use of 7.1% Chlorhexidine Digluconate (CHX) gel that releases 4% chlorhexidine for newborn umbilical cord care under a managed access program (MAP) implemented in Bungoma County of Kenya. Understanding the perspectives of providers regarding CHX is important since they play a key role in the health system and the fact that their views could be influenced by prior beliefs and inconsistent practices regarding umbilical cord car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
0
25
1
Order By: Relevance
“…There have also been unverified reports of an increase in the number of septic cords in the child welfare clinic . This is in contradiction to the findings reported in a study done in 2016 that showed high acceptability of CHX owing to its fast action in cord drop off (22).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There have also been unverified reports of an increase in the number of septic cords in the child welfare clinic . This is in contradiction to the findings reported in a study done in 2016 that showed high acceptability of CHX owing to its fast action in cord drop off (22).…”
Section: Discussioncontrasting
confidence: 99%
“…Methylated spirit, normal saline are among the most common products used for cord care (22). The same problem still exists today in our facility with most of the healthcare workers still not sure which product to use despite the guidelines being clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health care providers accepted use of CHX gel and were largely influenced by positive outcomes including ease of use, fast healing of the cord, minimal side effects and reduced infections based on records and mothers’ reports [ 16 ]. The evaluation presented similar results to ZamCAT as mothers and health workers agreed that chlorhexidine should continue to be freely provided through government health facilities and the importance of education and training for mothers and health providers prior to use [ 17 ].…”
Section: Discussionmentioning
confidence: 85%
“…While there are no reports of chlorhexidine being considered harmful when used appropriately to treat umbilical cord infections, it is important to correct the misperception that there are no risks associated with chlorhexidine use. A controlled managed access program was implemented in Bungoma County, Kenya to evaluate the acceptability of 7.1% chlorhexidine gel for neonatal umbilical cord care among providers and mothers of newborns [ 17 ]. Health care providers accepted use of CHX gel and were largely influenced by positive outcomes including ease of use, fast healing of the cord, minimal side effects and reduced infections based on records and mothers’ reports [ 16 ].…”
Section: Discussionmentioning
confidence: 99%